Plate-Like LiFePO₄ Nanoparticles: Synthesis, Structure, Electrochemistry - Kotsyubynsky, V.O.; Ostafiychuk, B.K.; Lisovsky, R.P.; Moklyak, V.V.; Hrubiak, A.B.; Hryhoruk, I.I.; Al-Saedi Abdul Halek Zamil (Наносистеми, наноматеріали, нанотехнології, 2017)
Гидротермальным синтезом получены пластинчатые частицы литий-железного фосфата размерами 100–150 нм и толщиной до 10 нм. Целью было исследование влияния относительного содержания этиленгликоля и температуры реакционной среды на фазовый состав полученных материалов, их кристаллическую и магнитную микроструктуры, состояние поверхности и электрические свойства. Установлено, что имеется корреляция между морфологией материалов и их электрохимическими свойствами. Уменьшение размера частиц и степени агломерации приводит к увеличению удельной ёмкости литиевых источников энергии с катодами на основе синтезированных материалов. Гідротермічною синтезою одержано платівчасті частинки літій-залізного фосфату розмірами у 100–150 нм і товщиною до 10 нм. Метою було дослідження впливу відносного вмісту етиленгліколю та температури реакційного середовища на фазовий склад одержаних матеріялів, їхні кристалічну та магнетну мікроструктури, стан поверхні й електричні властивості. Визначено, що є кореляція між морфологією матеріялів та їхніми електрохемічними властивостями. Зменшення розміру частинок і ступеня аґломерації приводить до підвищення питомої місткости літійових джерел живлення з катодами на основі синтезованих матеріялів. Lithium iron phosphate plate-like particles of 100–150 nm sizes and to 10 nm thickness have been obtained by hydrothermal synthesis. It has been aim to investigate influence of ethylene glycol relative content and reaction medium temperature on the obtained-materials’ phase composition, crystalline and magnetic microstructure, surface condition and electrical properties. As determined, there is correlation between the materials’ morphology and their electrochemical properties. The reducing of a particle size and agglomeration degree leads to specific capacity growing for lithium power sources with cathodes based on synthesized materials. The publication contains the results of studies conducted under the President’s of Ukraine grant for competitive projects of the State Fund for Fundamental Research.